Biocomposites: A Sinusoidally Architected Helicoidal Biocomposite (Adv. Mater. 32/2016). Issue 32 (August 2016) - Yaraghi, Nicholas A.; Guarín‐Zapata, Nicolás; Grunenfelder, Lessa K.; Hintsala, Eric; Bhowmick, Sanjit; Hiller, Jon M.; Betts, Mark; Principe, Edward L.; Jung, Jae‐Young; Sheppard, Leigh; Wuhrer, Richard; McKittrick, Joanna; et al.
Abstract : This artistic rendering depicts the mantis shrimp, an aggressive marine crustacean, employing its hammer‐like dactyl appendages to smash through the tough exoskeletal structure of its hard‐shelled prey with tremendous force and speed. In the work presented on page 6835, D. Kisailus and co‐workers uncover a unique ultrastructural motif within the dactyl impact surface that exhibits enhanced energy absorption and out‐of‐plane stiffness compared to traditional arthropod cuticle designs.